1985
DOI: 10.1111/j.1471-0528.1985.tb03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency is not a cause for abortion, congenital abnormality and small‐for‐gestational age infant in Chinese women

Abstract: Summary. Zinc concentration in serum and hair was measured in a cross‐sectional study of 437 Chinese women of whom 310 were normal controls studied at various stages of pregnancy and up to 12 months after delivery. The rest had spontaneous abortions, fetuses with a birthweight below the 10th centile for gestation or congenital abnormalities. Zinc concentration fell throughout normal pregnancy, the fall being greater in serum than in hair. There was no correlation between serum and hair levels. The infant birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…A study in the USA also found that, among both white and black mothers, serum zinc concentration was significantly related to birthweight after various independent determinants of birthweight were controlled (36). A similar association was also documented by studies in Turkey (37), India (38), and China (39). …”
Section: Discussionsupporting
confidence: 85%
“…A study in the USA also found that, among both white and black mothers, serum zinc concentration was significantly related to birthweight after various independent determinants of birthweight were controlled (36). A similar association was also documented by studies in Turkey (37), India (38), and China (39). …”
Section: Discussionsupporting
confidence: 85%
“…Twelve studies were identified that measured maternal circulating zinc in countries where inadequate zinc intake is predicted to be <17%, and looked at the association with birthweight (Table 1) [38,46,47,48,49,50,51,52,53,54,55,56]. Only one study, based on 3817 women in China, reported a 3.4-fold increase in the risk of delivering a LBW infant with serum zinc <560 µg/L (adjusted RR: 3.41, 95% CI: 1.97, 5.91) [56].…”
Section: Resultsmentioning
confidence: 99%
“…A further two studies reported circulating zinc to be lower in women who developed severe PE (blood pressure BP ≥ 160/110) compared to women whose pregnancies remained uncomplicated [73,74]. The remaining eight studies, whose sample sizes ranged from 10–271 women with PE/GH and 10–2038 women with an uncomplicated pregnancy, reported no difference in maternal zinc status between women with a hypertensive disorder of pregnancy and those without [38,47,54,75,76,77,78,79]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its antioxidant properties zinc plays an important role in normal growth and development and biological functions such as protein synthesis and nucleic acid metabolism. 415,416 Since these are involved in cell division and growth, zinc is believed to be important for fetal growth and development. 417 The review of antioxidants (vitamins C, E and D, and zinc) included 15 RCTs (n = 4763) [418][419][420][421] with one RCT 422 added to the primary studies identified in these earlier reviews.…”
Section: Antioxidantsmentioning
confidence: 99%